Genetic parameters of production and reproduction traits of Mediterranean buffaloes under tropical conditions - Iván A. Cárdenas; Miguel A. Chacón (Revista Científica)
In the tropics, there needs to be more information on Mediterranean buffaloes’ productive and reproductive behavior. For this reason, the zootechnical performance of a herd of Mediterranean buffaloes in Puerto Concha, Zulia state, Ven-ezuela, was evaluated. The phenotypic behavior and genetic parameters of the characteristics of milk yield (MY), lactation length (LL), calving interval (CI), age at first calving (AFC), and peak lactation (PLAC) were analyzed. The evaluated data comes from the genetic center “Hacienda Caño Negro” and corresponds to the productive and reproductive records from 2004 to 2021, inclusive. Descriptive statistics and analysis of variance were carried out for the mentioned characters. The variance components and genetic parameters of MY, LL, CI, and AFC were estimated using the mixed model methodology with an animal model in the MTDFREML program. After filtering and validating records, the information of 2350 closed lactations in the 18 years under study was available. The unadjusted and adjusted average for MY was 1819.5±10.7 kg and 1864.0±10.1 kg, respectively. The adjusted mean for LL and CI was 290.5±3.9 days and 477.4±3.6 days, respectively. The AFC average was 38.5±1.2 months. The PLAC is reached on average at 36 days with 8 kg of milk. The PLAC is achieved at 48 days with an average of 6.8 kg of milk for the first calving buffaloes. Concerning the genetic analysis, 3142 pedigrees were read, and 3243 individuals made up the relationship matrix. There are 732 inbred animals, with an average consanguinity of 4.2%. The heritability coefficient estimates were 0.37, 0.13, 0.05, and 0.27 for MY, LL, CI, and AFC, respectively. The moderate heredity index obtained for total milk production indicates the possibility of genetic improvement of this trait through selection programs. At the same time, the low heritability estimate for the calving interval reveals that the greatest variation in reproductive traits can be due to non-genetic factors, so the strategies to be followed for the progress of these characters in the herd will obey more to improvements in their management and environmental conditions.